2011
DOI: 10.1088/1748-3182/6/1/016009
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics and aerodynamics measurements of biologically inspired flexible flapping wings

Abstract: Flapping wing flight as seen in hummingbirds and insects poses an interesting unsteady aerodynamic problem: coupling of wing kinematics, structural dynamics and aerodynamics. There have been numerous studies on the kinematics and aerodynamics in both experimental and computational cases with both natural and artificial wings. These studies tend to ignore wing flexibility; however, observation in nature affirms that passive wing deformation is predominant and may be crucial to the aerodynamic performance. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Similar results were found experimentally by Barannyk et al (2012). However, other works (Heathcote and Gursul, 2007;Michelin and Llewellyn Smith, 2009;Ramananarivo et al, 2011;Spagnolie et al, 2010;Wu et al, 2011) have shown that under certain conditions more rigid foils actually achieve higher performance. Generally, in these works, it was found that the best performance is achieved when the degree of flexibility is chosen so that the passive deformation occurs at the appropriate phase with respect to the driven motion (Ramananarivo et al, 2011;Spagnolie et al, 2010) or provides the greatest amplification of the input motion (Michelin and Llewellyn Smith, 2009).…”
Section: Introductionsupporting
confidence: 85%
“…Similar results were found experimentally by Barannyk et al (2012). However, other works (Heathcote and Gursul, 2007;Michelin and Llewellyn Smith, 2009;Ramananarivo et al, 2011;Spagnolie et al, 2010;Wu et al, 2011) have shown that under certain conditions more rigid foils actually achieve higher performance. Generally, in these works, it was found that the best performance is achieved when the degree of flexibility is chosen so that the passive deformation occurs at the appropriate phase with respect to the driven motion (Ramananarivo et al, 2011;Spagnolie et al, 2010) or provides the greatest amplification of the input motion (Michelin and Llewellyn Smith, 2009).…”
Section: Introductionsupporting
confidence: 85%
“…For example, extensive experimental and numerical studies have been conducted on the effects of wing geometrical [14][15][16] (including wing aspect ratio, area, span et al) and on both lift and power consumption. Wing passive deformations beneficial for lift augment and power efficiency enhancement have also been discovered [17][18][19][20]. Then, various MAV prototypes using gear transmission, piezoelectric as well as electromagnetic drives were built, such as Robobee [21] of Harvard University, hummingbird [22] of AeroVironment Inc., KU Beetle [23] of Konkuk University, and Colibri [24] of ULB.…”
mentioning
confidence: 99%
“…The hand-layup technique used in this study was subsequently extended to a flapping platform [20], tested experimentally, and compared with a computational model [21]. This manufacturing process was also adopted in an experimental investigation of the deformation during flapping [22], recovering the importance of flexibility in the production of aerodynamic thrust force. Many studies use a similar fabrication process, using carbon fiber skeletons with a thin membrane constructed with a combination of handassembled and commercially available parts [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%